Generando valor compartido público: la importancia del análisis económico del derecho en la función normativa regulatoria del estado - Correa Zúñiga, César Luis (2023)
The purpose of this paper is to analyze the importance of creating shared value following the postulates of Michael E. Porter and Mark R. Kramer, and thus highlight the importance of the law and economics in the exercise of the regulatory power of the state, specifically in the formulation of laws and regulations by the Legislative and Executive Branch respectively, in order to generate a favorable and tangible impact on society and therefore, avoid an over and excessive regulation, starting by understanding and respecting the role of the state today, which should focus on guidance and economic promotion through good regulation.